2021
DOI: 10.1002/ep.13663
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of different diesel engines fueled with 1‐pentanol and diesel blends

Abstract: 1-pentanol has been gathering attention because of its advantages over the lower alcohols, and the researchers consider that it is a promising alternative fuel for diesel engines. In this study, two types of diesel engines were fueled with various blends of 1-pentanol (5%-35%) and diesel blends. Engine tests were performed using Onan DJC and Subaru RGD (3300H) unmodified diesel engines under different engine loads and speeds and results were reported and compared for both diesel engines.Test results of Onan an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 55 publications
(100 reference statements)
3
30
0
Order By: Relevance
“…Due to the fact that the physical parameter predictable "Z" is based on independent variables (Z 1 , Z 2 , Z 3 , Z 4 , … P n ), errors with a magnitude of "P" would be assessed by Equation (2), which is dependent on error independent variables, belongs to the accuracy of instruments, and Y 1 is the measured output. Then the overall uncertainties would be estimated by percentage uncertainties, as shown in the example.…”
Section: Analysis Of Errors and Uncertainties Of The Research Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that the physical parameter predictable "Z" is based on independent variables (Z 1 , Z 2 , Z 3 , Z 4 , … P n ), errors with a magnitude of "P" would be assessed by Equation (2), which is dependent on error independent variables, belongs to the accuracy of instruments, and Y 1 is the measured output. Then the overall uncertainties would be estimated by percentage uncertainties, as shown in the example.…”
Section: Analysis Of Errors and Uncertainties Of The Research Workmentioning
confidence: 99%
“…In response to the high demand for energy, governments are rushing to create a solid alternative renewable energy source, accelerated by rising emissions and the depletion of fossil fuel reserves. 1,2 It is necessary to use complete diesel fuel replacements such as ethanol and methanol and other engine modifications that are very expensive. 3 Partially replacing fossil fuels with biofuels, on the other hand, always helps to reduce emissions while also being costeffective.…”
Section: Introductionmentioning
confidence: 99%
“…Although 1-pentanol has many advantages over other alcohols, a definite mixing ratio cannot be recommended in the current literature for its use as a co-solvent in diesel-biodiesel mixtures and for emission reduction purposes. Determination of optimum concentrations in a three-component mixture is a performance-requiring process both in terms of time and economy [24][25][26][27][28]. At this point, the response surface methodology, which is one of the statistical methods applied based on the experimental design, stands out as an effective method in determining the optimum concentration of the three components [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Atmanli et al 15 compared the performance of various diesel engines (Onan DJC and Subaru RGD) that were powered by 1-pentanol and diesel blends. For higher blends of 1-pentanol/ diesel, the experimental results showed that BTE decreased while BSFC and EGT increased.…”
Section: Introductionmentioning
confidence: 99%